A TikTok™ "Benadryl Challenge" death—A case report and review of the literature. Issue 1 (29th September 2022) - Elkhazeen, Abu; Poulos, Chris; Zhang, Xin; Cavanaugh, John; Cain, Matthew
Abstract: TikTok™, a social media platform popular with teenagers and young adults, hosts a variety of short‐form user videos with durations from 15 s to 10 min. Among these videos are potentially dangerous "challenges, " such as the "Skull Breaker" challenge and the "Benadryl" challenge. Benadryl (diphenhydramine) is an over‐the‐counter medication with potential for misuse in both suicidal and recreational purposes. We report the case of a 14‐year‐old girl who reportedly ingested an unknown amount of diphenhydramine while taking part in a TikTok™ social media challenge. Autopsy revealed marked bilateral pulmonary congestion and edema, as well as a bright pink granular material within the esophagus, stomach, duodenum, and proximal jejunum. A postmortem femoral blood sample result identified a lethal blood concentration of diphenhydramine (49, 658 ng/ml). Physicians and other healthcare providers need to be aware of social media trends that may pose public health threats. Teenagers are a particularly susceptible group and need to be informed of the risks associated with these "challenges." For the forensics field, a knowledge of and process for accessing social media platforms can be critical for investigating deaths. Given the extremely elevated concentration of diphenhydramine in this case, a knowledge of circumstances of death, the scene, and social media trends can assist the forensic pathologist in determining the correct manner of death—accident versus suicide.